Reading-based holistic language learning program / Ananda Tilaka Sekara - Sekara, Ananda Tilaka (UPENA, 2006)
This Holistic Language Learning Program (HLLP) first grew out of the frustrations of the traditional intensive reading programs. Then, over the past fifteen years, the HLLP developed as an integral component of the larger Holistic Approach to ESL initiated at MARA Institute of Technology in 1986. It requires tertiary students studying for their diplomas or degrees to read an average of twelve selfselected magazine, newspaper or journal articles a semester and work on specific reading, writing, grammar and oral presentation tasks following a structured Holistic Language Learning Format (HLLF). Once a week, students present and discuss their articles in class. Students at Universiti Teknologi MARA have found the program extremely beneficial because much new and useful information is disseminated from so many different sources, grammatical features are studied in meaningful contexts and most importantly students are very actively involved in learning. The most useful part of the HLLP has been the "RESPONSE" section which has proved that given the freedom and opportunity students can be motivated to read, think and write excellent responses to ideas or arguments in the text. There is exposure to an unlimited amount of real language use. On the average it was found that about 5% of the students turned in excellent products, 20% very good products, 30% good products, 25% fairly good, and 20% poor products.